The Historical Development of Settlement by Aryan People in Terai of Nepal - Kafle, Dol Raj (Historical Journal, 2022)
This research article is related to the development of settlement by Aryan people in the Terai region of Nepal. Aryan people had entered the Terai region of Nepal during the Vedic period. In ancient times, various states were developed in the region of Nepal. The Mithila state of the Eastern Terai, the Ramgram state western part of the Gandaki River and the Kapilvastu state west of the present Butwal region were developed in before the Christian era. Most of the people in those states also migrated from India. Even in the middle Age, a state called Tirahoot or Doya was developed in the eastern Terai region of Nepal. Although this kingdom came to an end in the 14thcentury AD. After the conquest of the eastern Terai region by the Sen Dynasty the king of Palpa, the three kingdoms of Makwanpur, Chaudandi and Vijaypur remained in that region till the time of unification by Prithvi Narayan Shah, the king of Gorkha. After the unification of Nepal, the ancient and medieval independent Terai regions were automatically included in the Kingdom of Nepal. The article clarifies that there has been continuous settlement in the Terai region of Nepal from ancient period to the present.